Circulatory cytokines during the piroplasm stage of natural Theileria annulata infection in cattle - Tumer, Kenan Cagri; Kizil, Meltem (Wiley, 2023)
The objective of the present study was to investigate the inflammatory and anti-inflammatory cytokine response from a broad perspective in cattle with natural Theileria annulata infection. Ten cattle naturally infected with T. annulata and eight healthy cattle were included in this study. A total of 11 cytokines, including tumour necrosis factor-alpha (TNF-alpha), interferon-gamma (IFN-gamma), interleukin (IL)-1 beta, IL-2, IL-4, IL-5, IL-6, IL-10, IL-12, IL-13, and IL-17 were evaluated in serum samples using commercially available enzyme-linked immunosorbent assay (ELISA) kits. There was no statistical significance for serum TNF-alpha, IL-1 beta, IL-5, IL-6, and IL-17 levels between the T. annulata infected and healthy cattle. In contrast, the median serum levels of IFN-gamma (p = .023), IL-2 (p = .066), IL4 (p = .0016), IL-10 (p = .00087), IL-12 (p = .00018), and IL-13 (p = .023) were significantly higher in T. annulata-infected cattle than in healthy cattle. The results of the present study revealed that in the intraerythrocytic stage of tropical theileriosis, a very pronounced anti-inflammatory response occurs as well as an ongoing inflammatory process.
Keywords: cytokine; piroplasm stage; T. annulata; tick